POPULATION RADIATION PROTECTION PROVIDING UNDER THE INFLUENCE OF NATURAL IONIZING IRRADIATION SOURCES - E. G. Stepanov; A. S. Zherebcov; Sh. Z. Gilmanov; I. I. Khisamiev; E. S. Shakirova; O. V. Tuvanyaeva (Радиационная гигиена, 2015)
An article presents the modern problems of population radiation protection inBashkortostanRepublic. The main natural ionizing irradiation sources are identified and their contribution to the total exposure dose of the BashkortostanRepublicpopulation is analyzed. The types of the main natural ionizing irradiation sources are identified, as well as the ways of their intake and the methods of their influence. The results of laboratory studies are presented for the radon equivalent equilibrium volumetric activity, for the average gamma radiation dose rate in dwellings, for the investigations of gross alpha and gross beta activity in drinking water and open water sourcesBashkortostanRepublic. The article underlines the main problems of the radiation situation in the new construction. The main preventive measures are pointed out for the radiation protection of the buildings under construction improving. The article also presents an analysis of the results of activities of the Administration of Rospotrebnadzor in theBashkortostanRepublicfor the reducing of the levels of the Republican population exposure from the natural irradiation sources.